2018
DOI: 10.1103/physrevaccelbeams.21.041001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the resistive wall impedance on beam dynamics in the Future Circulare+eCollider

Abstract: The Future Circular Collider study, which aims at designing post-LHC particle accelerator options, is entering in the final stage, which foresees a conceptual design report containing the basic requirements for a hadron and a lepton collider, as well as options for an electron-proton machine. Due to the high beam intensities of these accelerators, collective effects have to be carefully analyzed. Among them, the finite conductivity of the beam vacuum chamber represents a major source of impedance for the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…As it can be seen, for the above assumptions, the real part of the impedance does not depend on the coating thickness and conductivity. The performed numerical studies [13] have confirmed that the resulting RF power losses due to the RW impedance remain almost unchanged for the coating conductivity and thickness varying in a very wide range. In turn, since the perturbation of the imaginary part due to the coating is proportional to its thickness and to the term (1 − 1 2 ), if the coating conductivity is much smaller than the beam pipe material conductivity the impedance depends only on the thickness of the coating layer.…”
Section: Beam Coupling Impedancementioning
confidence: 59%
See 2 more Smart Citations
“…As it can be seen, for the above assumptions, the real part of the impedance does not depend on the coating thickness and conductivity. The performed numerical studies [13] have confirmed that the resulting RF power losses due to the RW impedance remain almost unchanged for the coating conductivity and thickness varying in a very wide range. In turn, since the perturbation of the imaginary part due to the coating is proportional to its thickness and to the term (1 − 1 2 ), if the coating conductivity is much smaller than the beam pipe material conductivity the impedance depends only on the thickness of the coating layer.…”
Section: Beam Coupling Impedancementioning
confidence: 59%
“…As it has been shown in [13], for the 100 km long collider, the finite conductivity of the beam vacuum chamber represents a major source of the beam coupling impedance, and wake fields strongly affect the beam dynamics and, respectively, collider design solutions and parameters choice. This fact has been taking into account while choosing the vacuum chamber shape and its dimensions.…”
Section: Beam Coupling Impedancementioning
confidence: 99%
See 1 more Smart Citation
“…The coupling impedance [1][2][3][4][5] due to the finite resistivity of the beam vacuum chamber, generally called resistive wall impedance, can represent an important source of impedance, as, for example, in LCLS undulator [6], or even the main contributor, as in the case of the Future Circular Collider project [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Collective effects due to self-induced electromagnetic fields in a particle accelerator are generally studied by introducing the concepts of wakefield and coupling impedance [1][2][3], which represent, in time and frequency domain respectively, the response of the environment to a point charge traveling inside the beam vacuum chamber or in any of the accelerator devices. These effects can be very important [4], and in some cases they could compromise the machine performance leading to partial or total beam losses [5]. For low energy accelerators with nonrelativistic beams, a not negligible contribution to the total impedance is given by the so-called space charge effects [6,7], which are generated directly by the charge distribution and indirectly by the image charges on the pipe wall.…”
Section: Introductionmentioning
confidence: 99%